PENGARUH DER, PDB DAN EPS TERHADAP HARGA SAHAM PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI - Putri Aulia Febrianti; Nurhayati Nurhayati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This research purpose is to discover the influence of Debt Equity Ratio (DER), Gross Domestic Product (GDP), and Earning Per Share (EPS) to The Price of stocks of insurance company which are listed in Indonesia Exchange Stock. The research method used in this study is quantitative research methods. The sample is 5 insurance companies listed in Indonesia Exchange Stock which were previously determined by the purposive sampling method. Data collected in the form of annually financial reports for each Insurance companies listed in Indonesia Exchange Stock from 2014 -2018 The analysis technique used is panel data regression. Based on the analysis conducted stated that DER has a negative effect on the stock prices of insurance companies and GDP, EPS has a positive influence on the stock prices of insurance companies listed on the Indonesian Exchange Sctock. However, on the other hand the growth of gross domestic product has a direct and significant effect on the value of shares of insurance companies listed on the Indonesian Exchange Stock.